The computer simulation of cellular automata traffic model with the consideration of vehicle-to-infrastructure communication technology. (November 2020) - Małecki, Krzysztof; Gabryś, Maciej
Based on the two-lane, symmetric traffic model (STCA), a modified traffic model, including Vehicle-to-Infrastructure (V2I) communication (STCA V2I model, for short), is presented. The combined full-autonomous and semi-autonomous vehicles are able to exchange information as well as the intentions of the driver with the surrounding vehicles through V2I communication. In the analyzed case, the communication between vehicles includes the sending of information to vehicles to the rear about the traffic situation ahead. Numerical simulations present a greater dispersion of vehicles with the same traffic density and fewer lane changes, while maintaining the same average vehicle speed as in the STCA model. Spatial–temporal profiles of traffic flow indicate that vehicles moving in accordance with the STCA V2I model are not subject to unnecessary concentration. Numerical studies have shown the positive and negative effects of transmitting traffic congestion messages.